Pengaruh Skeptisme Profesional, Independensi, Tekanan Waktu Dan Gender Terhadap Kemampuan Auditor Dalam Mendeteksi Kecurangan (Fraud): (Studi Empiris Pada Perwakilan BPKP Provinsi Riau) - Aswanda, Nurul; Putri, Annie Mustika; Putri, Adriyanti Agustina (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
This study aims to determine the effect of professional skepticism, independence, time pressure and gender on the auditor’s ability to detect fraud. The sample in this study were all auditors working at the BPKP Representative Office Of Riau Province, totaling 78 poeple. This type of research is a quantitative research. The data analysis method used was linear multiple analysis, the data were processed using SPSS software version 26. Partial result showed that the variables of professional skepticism, independence, time pressure and gender had a significant effect on the auditor’s ability to detect fraud. And the results of the study simulyaneously show that professional skepticism, independence, time pressure and gender have a joint effect on the auditor’s ability to detect fraud.